Stability test of the silicon Fiber Bragg Grating embroidered on textile for joint angle measurement - Apiwattanadej, Thanit (2019)
Recently, Fiber Bragg Grating (FBG) sensors are being used for motion tracking applications. However, the sensitivity, linearity and stability of the systems have not been fully studied. Herein, an embroidered optical Fiber Bragg Grating (FBG) on a stretchable supportive textile for elbow movement measurement was developed. The sensing principle of this system is based on the alteration of Bragg wavelength due to strain from the elbow movements. The relationship between elbow movements and reflected Bragg wavelength was found to be linear. The dynamic range of FBG sensor on elbow support is between 0 and 120 degree. Finally, the stability of the FBG sensor on the supportive textile was tested during the exercise and the cleaning process with water. The sensitivity of FBG sensors for joint angle measurement and the effect of the movement and cleaning process to signals from FBG sensors after using in the real activity will be the basis knowledge for design and actual implementation of future optical fiber based wearable devices.